Bacterial pathogens causing neonatal sepsis in Peru: a systematic review - Gonzales, Antony (2024)
Neonatal sepsis is an important cause of mortality worldwide, with a heterogeneous clinical presentation that makes early diagnosis difficult. In Peru, it represents the main cause of death in infants under one year of age, with coagulase-negative Staphylococcus being identified as the most frequent causal pathogen. However, microbiological characterization and analysis of bacterial resistance in the Peruvian neonatal population is still limited. The objective was to determine the microbiological characteristics and resistance profile of microorganisms causing neonatal sepsis in Peru. The study was carried out following the PRISMA Guidelines and the protocol was registered in PROSPERO (International prospective register of systematic reviews; CRD42024506552). PubMed/MEDLINE, LILACS, SciELO, Scopus and Web of Science were searched systematically from their inception until February 16, 2024. Quality was assessed using the Agency for Healthcare Research and Quality (AHRQ) checklist for cross-sectional studies and the Newcastle-Ottawa scale for cohort studies. Of 647 studies identified, 15 were selected for full evaluation. Six studies were included in the final analysis, covering a period from 2016 to 2022. Two articles were considered of good quality and four of medium quality. In five of the six studies Staphylococcus coagulase negative was the most frequently isolated bacterium. Extended-spectrum beta-lactamase (ESBL)-producing bacteria were reported in 4 of the 6 studies ranging from 8.2 to 83.1%. The combination of ampicillin with some were the most frequently used as first line. The reports considered revealed that the most frequent causative agent in neonatal sepsis was coagulase-negative Staphylococcus. The most frequent resistance pattern isolated was BLEE production and the first line antimicrobial therapy was ampicillin in combination with some aminoglycoside.